Penerapan Prinsip Una Via sebagai Restorative Justice dalam Kejahatan Pasar Modal oleh Otoritas Jasa Keuangan - Ariyanti, Nur Hasanah; Anjani, Citra Delia (Media Hukum Indonesia (MHI), 2024)
The capital market exerts a significant influence on the state's economy. The practice of capital markets in Indonesia has demonstrated a consistent upward trajectory over recent years, accompanied by a parallel increase in the incidence of capital market crime. Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector introduced a novel principle in the capital market, the una via principle. This principle represents an implementation of restorative justice for addressing capital market crimes. The una via principle empowers the Financial Services Authority (OJK) as an investigator have the authority to determine the appropriate sanctions for alleged capital market crimes, between criminal sanctions or administrative sanctions. In practice, the application of the una via principle lacks clearly defined procedures and parameters, raising concerns that it may not fully achieve the purpose of restorative justice, ensuring the fairest possible outcome for all parties involved. This research employs a normative juridical approach, utilizing descriptive analysis. Additionally, it incorporates qualitative juridical data analysis. Based on the findings, it can be concluded that the implementation of the una via principle as restorative justice still necessitates refinement, particularly in terms of regulation and execution, due to the persistence of certain deficiencies.